The Effect of Organizational Trust, Perceived Organizational Support (POS) and Innovative Work Behavior (IWB) on University Performance during Digital Era - Khiong, Khie; Utomo, Budi (International Journal of Social and Management Studies, 2023)
This research aims to investigate the relationship between perceived organizational support (POS) and organizational trust, investigate the relationship between innovative work behavior (IWB) and organizational trust, investigate the relationship between perceived organizational support (POS) and performance, and investigate the relationship between innovative work behavior ( IWB) on performance, investigated the relationship between organizational trust and performance variables. This type of research is quantitative research. Each research indicator was measured using a Likert scale of 1-7 points and criteria from strongly agree to strongly disagree. The analytical tool used in this study was SEM based on PLS (Partial Least Square). The respondents to this study were 310 university lecturers in Banten Indonesia who were determined using the simple random sampling method. The research data was obtained by distributing online questionnaires through social media. The results of the hypothesis test showed that The results of the hypothesis test show that the perceived organizational support (POS) variable has a significant effect on organizational trust, the innovative work behavior variable (IWB) has a positive and significant effect on organizational trust, the perceived organizational support (POS) variable has a positive and significant effect on performance, the innovative work variable work behavior (IWB) has a positive and significant effect on performance, organizational trust variables have a significant effect on university performance.